Stroke rehabilitation adaptive approaches: A theory-focused scoping review - Mary Egan; Dorothy Kessler; Nalia Gurgel-Juarez; Anchal Chopra; Elizabeth Linkewich; Lindsey Sikora; Phyllis Montgomery; Patrick Duong (Scandinavian Journal of Occupational Therapy)
Background Stroke rehabilitation consists of restorative and adaptive approaches. Multiple adaptive approaches exist.Aims/Objectives The objective of this study was to develop a framework for categorising adaptive stroke rehabilitation interventions, based on underlying theory.Material and Methods We searched multiple databases to April 2020 to identify studies of interventions designed to improve participation in valued activities. We extracted the name of the intervention, underlying explicit or implicit theory, intervention elements, and anticipated outcomes. Using this information, we proposed distinct groups of interventions based on theoretical drivers.Results Twenty-nine adaptive interventions were examined in at least one of 77 studies. Underlying theories included Cognitive Learning Theory, Self-determination Theory, Social Cognitive Theory, adult learning theories, and Psychological Stress and Coping Theory. Three overarching theoretical drivers were identified: learning, motivation, and coping.Conclusions At least 29 adaptive approaches exist, but each appear to be based on one of three underlying theoretical drivers. Consideration of effectiveness of these approaches by theoretical driver could help indicate underlying mechanisms and essential elements of effective adaptive approaches.Significance Our framework is an important advance in understanding and evaluating adaptive approaches to stroke rehabilitation.